The use of Indicators of Educational Quality: A Critical Discussion from the Chilean Case - Galioto, Carmelo (2022)
Introduction. Contemporary educational policies for school systems emphasize the evaluation of educational quality through results obtained from standardized tests or performance indicators. Purpose. To develop a problematization of the operationalization and standardization of the notion of quality in school education, taking as a case study the decision of the Chilean Educational Quality Agency to introduce indicators of personal and social development.  Discussion. The essay uses the notion of audit culture from the socio-anthropological literature and the reflections of Hannah Arendt in order to problematize the use of indicators in the field of educational policies for primary and secondary schools. In the first instance, it is argued that these evaluation indicators are framed in what the scientific literature has defined as an “audit culture” and, in particular, in an aspect of it that has been coined as the “indicator game.” In the second instance, it is argued that these indicators are insufficient to account for personal and social development; this is shown by proposing a substantive definition of school education obtained from Hannah Arendt: a phenomenon that inserts the novelty represented by the students into the world. Conclusions. These measurement indicators of quality inevitably reduce the phenomenon to be measured. Notwithstanding the foregoing, the attention of educational policies to a substantive aspect such as personal and social development can be used to discuss what school education we are thinking about and designing.